2001
DOI: 10.1038/sj.cgt.7700284
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus–adenovirus receptor expression in ovarian cancer cell lines is associated with increased adenovirus transduction efficiency and transgene expression

Abstract: The expression of coxsackievirus ± adenovirus receptor ( CAR ) and the integrins v 3 and v 5 was analyzed quantitatively ( flow cytometry ) and qualitatively ( immunocytochemistry ) in five human ovarian cancer cell lines ( PEO1, PEO4, PEO14, SKOV -3, and OVCAR -3 ) and three control cell lines ( 293, HeLa, and CHO -K1 ) . The transduction efficiencies were evaluated by adv / rsv --Gal transduction followed by X -gal staining. The effects of 17 -estradiol on cell growth, CAR and integrins v 3 / 5 expression, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 16 publications
1
43
0
Order By: Relevance
“…13,24,28,29 However, as many tumor cells tightly bind to each other or to normal stromal cells within tumor tissues, the preparation of single tumor cells is not easy, and therefore flow cytometry is an inadequate method for the detection of CAR expression in tumor tissues. In contrast, the preparation of single tumor cells is not necessary for the OBP-401-mediated GFP induction protocol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,24,28,29 However, as many tumor cells tightly bind to each other or to normal stromal cells within tumor tissues, the preparation of single tumor cells is not easy, and therefore flow cytometry is an inadequate method for the detection of CAR expression in tumor tissues. In contrast, the preparation of single tumor cells is not necessary for the OBP-401-mediated GFP induction protocol.…”
Section: Resultsmentioning
confidence: 99%
“…Flow cytometry is mainly used to detect CAR-positive human tumor cell lines. 13,24,28,29 Immunohistochemistry is frequently used to assess CAR expression in various human tumor tissues. 11,14,20,23,25 Western blotting is usually performed to confirm the expression of many types of proteins including CAR in molecular biological experiments.…”
Section: Introductionmentioning
confidence: 99%
“…22 The OVCAR-3 cell line used here expresses moderate levels of CAR. 23 In vitro infections followed by immunostaining for NIS revealed patchy positive staining that was both intracellular and membrane bound. The NIS protein must be targeted to the cell membrane to be functional.…”
Section: Discussionmentioning
confidence: 99%
“…22 For this reason, two adenoviral constructs containing NIS under the control of the (1) cytomegalovirus (CMV) or (2) MUC1 promoters were used to infect an ovarian cancer cell line (OVCAR-3), which had been reported to express moderate levels of CAR. 23 The potent nonspecific CMV promoter was initially used to determine whether functional NIS expression could be established in this model in vivo. Following successful therapy of CMV/ NIS-transduced tumors, the MUC1/NIS construct was used to provide transcriptional targeting to the MUC1-positive tumors and further reduce the risk of extratumoral toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…11 In contrast, on a panel of five ovarian cancer cell lines analyzed by flow cytometry and immunohistochemisty, the expression of the primary receptor, CAR, was found to be essential for adenoviral transduction efficiency, whereas integrin expression was not limiting. 12 Immunohistochemisty on ovarian cancer tissue from 37 patients with varying disease status showed that 97% were positive for CAR expression, whereas stromal and endothelial cells of the tumor were negative. 13 In addition, 62 and 65% of tumor tissues expressed a v b 3 and a v b 5 , respectively.…”
Section: Introductionmentioning
confidence: 98%